2020
DOI: 10.3390/ijerph17197281
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Voice Matters! Improving Smoking Prevention with Testimonial Messages through Identification and Cognitive Processes

Abstract: Narrative messages are increasingly being used in the field of tobacco prevention. Our study is based on narrative persuasion and aims to analyze the psychological mechanisms that explain why the narrative voice is relevant to promote persuasive impact. An online experiment with a 2 (narrative voice) × 2 (message) factorial design was carried out. Participants (525 adult smokers) were randomly assigned to two experimental conditions (first-person versus third-person narrative message). To increase the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…The testimonial message elaborated for this study had a clear and causal structure, in such a way that a series of events were presented that were connected in space and time (see Table 2 ). It was narrated in the first person, since previous research had concluded that the use of the first person was more effective than the second- or third-person narrative voice [ 42 , 47 ]. The message’s protagonist was a 23-year-old individual named Alex Sanchez (@sanchez98_alex).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The testimonial message elaborated for this study had a clear and causal structure, in such a way that a series of events were presented that were connected in space and time (see Table 2 ). It was narrated in the first person, since previous research had concluded that the use of the first person was more effective than the second- or third-person narrative voice [ 42 , 47 ]. The message’s protagonist was a 23-year-old individual named Alex Sanchez (@sanchez98_alex).…”
Section: Methodsmentioning
confidence: 99%
“…This process, in turn, would activate different routes to explain the persuasive impact: through identification with the protagonist, through narrative transportation and through reactance. However, in this work, we considered a fourth mechanism: cognitive elaboration [ 41 , 42 , 43 ]. Cognitive elaboration is defined as a process of reflection on the content of the message and constitutes a measure of the intensity of such reflection during the reception process [ 44 ].…”
Section: Narrative Persuasion With Testimonial Messages: Advancing Th...mentioning
confidence: 99%
“…First, BRC type, an independent variable, was coded as dummy variable (Narrative BRC = 1, non-narrative BRC = 0). This analysis provides the evaluation of the effect of experimental conditions on purchase intention, a dependent variable, through narrative transportation (primary mediator) and perceived purchase risks (secondary mediators) (Igartua & Rodríguez-Contreras, 2020). The results showed that BRC type significantly increased narrative transportation (b = 0.709, SE = 0.086, p < 0.001), and significantly lowered perceived financial risk (b = -0.178, SE = 0.069, p < 0.01).…”
Section: Test Of Serial-parallel Mediation Modelmentioning
confidence: 99%
“…Exposure to narratives is positively associated with narrative‐consistent beliefs, attitudes, intentions, and behaviors 7 . Narrative interventions may be particularly beneficial for early detection and prevention of cancer; they have been shown to influence engagement in cancer prevention 8,9 and screening behaviors 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…particularly beneficial for early detection and prevention of cancer; they have been shown to influence engagement in cancer prevention 8,9 and screening behaviors. 10,11 One method for increasing the effectiveness of narratives is incorporating behavior change theory.…”
mentioning
confidence: 99%